Perceived helicopter parenting and its association with coping skills and stress appraisals in Turkish youth athletes - Denizci, Tuba; Ozdurak Singin, Rabia Hurrem; Kaya, Hakan; Talaghir, Laurentiu-Gabriel; Iconomescu, Teodora Mihaela; Bentea, Cristina Corina (Frontiers in Psychology, 2025)
IntroductionHelicopter parenting (HP), characterized by overinvolved behaviors, may impact young athletes’ psychological skills. This study aimed to examine the relationship between perceived HP, athletic coping skills, and stress appraisals (challenge and threat) in Turkish competitive youth athletes aged 13–15 years.MethodsA total of 398 competitive youth athletes participated, with 302 categorized into HP (n = 51) or regular parenting (RP, n = 251) groups. The Perceived Helicopter Parenting Scale, Athletic Coping Skills Inventory-28, and Challenge and Threat in Sport Scale were administered at two time points: during a training session and within 30 minutes before a competitive event. Mann-Whitney U-tests and repeated-measures ANOVA were used for analysis.ResultsAthletes with HP parents reported significantly lower total coping skills (p = 0.001) and lower scores on all subscales except coachability (p < 0.05) compared to those with RP parents. Before competitions, HP athletes exhibited lower challenge (p < 0.001) and higher threat appraisals (p = 0.001), with no differences observed during training.DiscussionPerceived HP is associated with reduced coping skills and heightened threat appraisals in competitive contexts, highlighting the need for interventions to promote balanced parental involvement in youth sports.